2017
DOI: 10.1177/1470320317739987
|View full text |Cite
|
Sign up to set email alerts
|

Association of the genetic and traditional risk factors of ischaemic heart disease with STEMI and NSTEMI development

Abstract: Introduction:To evaluate the influence of traditional risk factors of ischaemic heart disease and genetic factors to predict different types of acute coronary syndromes.Materials and methods:Five hundred and twenty-three patients with acute coronary syndromes (393 with ST elevation myocardial infarction (STEMI) and 130 with non-ST elevation myocardial infarction (NSTEMI)) comprised the study group. The control group consisted of 645 subjects free from symptoms of ischaemic heart disease and stroke. Genetic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Patients from our study showed no difference according to the traditional risk factors (hypertension, diabetes mellitus, hypercholesterolemia, BMI, history of smoking and positive family history, for developing CAD and MI, in groups of STEMI and NSTEMI.Similar results were published in study of Ţaliaduonytė-Pekšienė D et al (22). No difference according to the coronary risk factors among patients with STEMI and NSTEMI were obtained in the study of Miyachi H et al (23).…”
Section: Discussionsupporting
confidence: 87%
“…Patients from our study showed no difference according to the traditional risk factors (hypertension, diabetes mellitus, hypercholesterolemia, BMI, history of smoking and positive family history, for developing CAD and MI, in groups of STEMI and NSTEMI.Similar results were published in study of Ţaliaduonytė-Pekšienė D et al (22). No difference according to the coronary risk factors among patients with STEMI and NSTEMI were obtained in the study of Miyachi H et al (23).…”
Section: Discussionsupporting
confidence: 87%
“…The cortisol index may be valuable at the discrimination of high versus low risk patients after AMI. The results of other studies demonstrate that other prognostic markers, such as troponin I and T, natriuretic brain peptides, cortisol, and even the genetic background, may be important if we wish to assess the risk of the fatal outcome [34]. However, our data demonstrates that the cortisol index if comparing to troponin I and cortisol is the most valuable predictor of mortality after AMI with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 58%
“…Although the diagnosis of MI has risen considerably by applying some specific gene biomarkers such as cardiac Troponin T/I, and CK-MB, but these biomarkers are not specific to distinguish NSTEMI and STEMI. Interestingly, NSTEMI and STEMI have different pathophysiologic conditions, indicating that the development and occurrence of MI may be strongly dependent on the different signaling pathways 26 , 27 . Therefore, the research on NSTEMI/STEMI-related genes may improve the diagnosis and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%